Cell‐Friendly Isolation and pH‐Sensitive Controllable Release of Circulating Tumor Cells by Fe3O4@CaCO3 Nanoplatform. Issue 21 (10th October 2021) - Wang, Peng; Xue, Junli; Wu, Shengming; Pei, Yanbai; Xu, Lehua; Wang, Yilong
Abstract: Circulating tumor cells (CTCs) have been recognized as significant research target for cancer prognosis and metastasis mechanism. Efficient and all‐subpopulations‐covered isolation and facile release of CTCs with good viability are pivotal for profound mechanism research and molecular profiling. However, integrated nanoplatform with these two functions is yet to be elucidated. Among existing release techniques including physical, biological, and chemical methods, acid responsive release of CTCs attracts intensive interests due to its straightforward and easily accessible feature. However, extra acidic substance seems indispensable so far, which poses potential hazard to the rare and susceptible CTCs. To address this challenge, polyelectrolyte functionalized CaCO3 coated magnetic nanocrystal clusters are developed as the nanoplatform for multi‐subpopulations isolation and pH‐sensitive release of CTCs. Only buffer solution components are needed rather than other acidic substance to provide mild acidic environment with pH value of 6.5, facilitate highly efficient release. Moreover, the bioefficacy of CTC capture and mild condition recovery is not compromised by formation of protein corona on the cell‐friendly nanoplatform. This nanoplatform exhibits good performance in both mimic blood samples and cancer patients' clinical samples. Abstract : For cancer prognosis and molecular profiling of the circulating tumor cells (CTCs), a novel biocompatible, protein corona interference resistant, and positively‐charged core‐shell inorganic nanocomposite Fe3 O4 @CaCO3 as a multifunctional nanoplatform to efficiently isolate the CTCs from the clinical blood and ascitic fluid samples and subsequently mild pH sensitive release with well‐maintained viability is developed.